Neuronal Nitric Oxide Synthase and NADPH Oxidase Interact to Affect Cognitive, Affective, and Social Behaviors in Mice - Walton, James C. (2013)
Both nitric oxide (NO) and reactive oxygen species (ROS) generated by nNOS and NADPH oxidase (NOX), respectively, in the brain have been implicated in an array of behaviors ranging from learning and memory to social interactions. Although recent work has elucidated how these separate redox pathways regulate neural function and behavior, the interaction of these two pathways in the regulation of neural function and behavior remains unspecified. Toward this end, the p47phox subunit of NOX, and nNOS were deleted to generate double knockout mice that were used to characterize the behavioral outcomes of concurrent impairment of the NO and ROS pathways in the brain. Mice were tested in a battery of behavioral tasks to evaluate learning and memory, as well as social, affective, and cognitive behaviors. p47phox deletion did not affect depressive-like behavior, whereas nNOS deletion abolished it. Both p47phox and nNOS deletion singly reduced anxiety-like behavior, increased general locomotor activity, impaired spatial learning and memory, and impaired preference for social novelty. Deletion of both genes concurrently had synergistic effects to elevate locomotor activity, impair spatial learning and memory, and disrupt prepulse inhibition of acoustic startle. Although preference for social novelty was impaired in single knockouts, double knockout mice displayed elevated levels of preference for social novelty above that of wild type littermates. These data demonstrate that, depending upon modality, deletion of p47phox and nNOS genes have dissimilar, similar, or additive effects. The current findings provide evidence that the NOX and nNOS redox signaling cascades interact in the brain to affect both cognitive function and social behavior.